2010
DOI: 10.1111/j.1582-4934.2010.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for the use of structural information and chemical genetics to develop inhibitors of Janus kinases

Abstract: Gain-of-function mutations in the genes encoding Janus kinases have been discovered in various haematologic diseases. Jaks are composed of a FERM domain, an SH2 domain, a pseudokinase domain and a kinase domain, and a complex interplay of the Jak domains is involved in regulation of catalytic activity and association to cytokine receptors. Most activating mutations are found in the pseudokinase domain. Here we present recently discovered mutations in the context of our structural models of the respective domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 276 publications
(309 reference statements)
2
79
0
Order By: Relevance
“…disease-causing JH1 and JH2 mutations localize in or near the JH2-JH1 interface and are expected to destabilize the interaction (13,18). The structures of JAK1 and TYK2 JH2 are highly similar to JAK2 JH2 (5,19), and all three JH2s bind ATP (20).…”
Section: Significancementioning
confidence: 90%
See 2 more Smart Citations
“…disease-causing JH1 and JH2 mutations localize in or near the JH2-JH1 interface and are expected to destabilize the interaction (13,18). The structures of JAK1 and TYK2 JH2 are highly similar to JAK2 JH2 (5,19), and all three JH2s bind ATP (20).…”
Section: Significancementioning
confidence: 90%
“…The V617F mutation is found in ∼95% of patients with polycythemia vera (PV) (9-12) as well as in ∼60% of patients with essential thrombocythemia (ET) and primary myelofibrosis (PMF). After identification of the V617F mutation, a multitude of other mutations in JAK2, JAK1, and JAK3 have been found that are linked to myeloid and lymphoid malignancies and to immunological diseases as well as to some solid cancers (13,14). The mutations cluster mainly in exon 12 in the SH2-JH2 linker (numbering for human JAK2), exon 14 near Val617, and exon 16 (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As in other protein kinases, ATP binding may prime for critical conformational changes (40,41). Indeed, structural studies showed that the isolated JH1 domains of the four Jaks complexed with ATP-competitive inhibitors adopt an active conformation with an exposed loop (42)(43)(44). With regard to intact Jaks, specific ATP competitive inhibitors that block catalytic function also promote activation loop phosphorylation in cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…8 Currently several JAK2 inhibitors are under development or/and undergoing clinical trials for MPNs. 27 Identification of JAK inhibitor-resistant mutations in JAK2 is, therefore, of great importance. We, therefore, introduced the Y931C, a homologous mutation of JAK1 F958C, into WT or V617F JAK2 protein and selected these cells for autonomous proliferation.…”
Section: Jak2 Y931c the Homologous Mutation Of Jak1 F958c Confers Rmentioning
confidence: 99%